FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KAPASITAS VITAL PARU TUKANG OJEK DI PELABUHAN SUKA BANGUN KABUPATEN KETAPANG - Wijayarsi, Dian; Trisnawati, Elly; Marlenywati, Marlenywati (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
Background: The environment is very risky to the health of motorcycle taxi drivers because it can affect the health of motorcycle taxi drivers which will cause bad effects especially on the respiratory system. Respiratory system disorders will reduce the ability of lung function, where the disorders of lung function decline can be found from the air volume. Based on the preliminary survey were conducted on 10 motorcycle taxi drivers, obtained information that 60% of vital capacity motorcycle taxi drivers had abnormal lung. The purpose of this research is to know related factors to lung vital capacity of motorcycle taxi drivers at the Port of Suka Bangun Ketapang. Methods: research observational analytic cross-sectional approach. with 54 motorcycle taxi drivers who worked at the Port of Suka Bangun Ketapang. The test used is the Chi-square test. Result: The research results showed that there was no significant correlation between age (p value = 0.718), duration of work / day (p value = 1.000), and nutritional status (p value = 0.355) to the lung vital capacity of motorcycle taxi drivers at the Port of Suka Bangun Ketapang and there was a significant association between smoking habits (p value = 0.003 ; PR = 2.514), the use of masks (p value = 0.034 ; PR = 1.948), and work times (p value = 0.014 ; PR = 2.632) to the lung vital capacity of motorcycle taxi drivers at the Port of Suka Bangun Ketapang. Suggestions : The Unity of Motorcycle Taxi Drivers Suka Bangun - is able to provide personal protective equipment standards as masks to protect the respiratory systems from harmful gases and for the motorcycle taxi drivers to be routinely checked on health cares.